1988
DOI: 10.1007/bf00257328
|View full text |Cite
|
Sign up to set email alerts
|

Repeated quantitative bone scintigraphy in patients with prostatic carcinoma treated with orchiectomy

Abstract: Bone scintigraphy was performed in 16 men with newly diagnosed prostatic carcinoma before orchiectomy as well as 2 weeks and 2 months after operation. The uptake in the lower thoracic and lumbar vertebrae was registered up to 240 min after injection of 99mTc-MDP and was then calculated for each patient and vertebra. The relative standard deviation in measured uptake due to measuring technique was estimated to be +/- 7%. In eight patients, who had normal bone scintigraphies before orchiectomy, there were no cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…However, it has been shown that the bone scan is limited in its sensitivity to measure treatment effect, with only 52% of responders showing scintigraphic improvement and 62% of non-responders showing scintigraphic deterioration at 6 to 8 months in one early study of patients with breast cancer [6]. In an attempt to increase sensitivity of response measurement, some authors have described various semi-quantitative means of following bone metastases with bone scintigraphy [7-10], but others have found no advantage over visual interpretation [11] and quantitative methods have not gained acceptance into routine practice.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been shown that the bone scan is limited in its sensitivity to measure treatment effect, with only 52% of responders showing scintigraphic improvement and 62% of non-responders showing scintigraphic deterioration at 6 to 8 months in one early study of patients with breast cancer [6]. In an attempt to increase sensitivity of response measurement, some authors have described various semi-quantitative means of following bone metastases with bone scintigraphy [7-10], but others have found no advantage over visual interpretation [11] and quantitative methods have not gained acceptance into routine practice.…”
Section: Introductionmentioning
confidence: 99%
“…The count rate from " m T c -M D P was determined over the lower thoracic and lumbar spine. In most of the patients with skeletal metastases the flare phenomenon, with an increase in count rate two weeks after orchiectomy followed by a decrease after two months, was seen as response to treatment (23,24,25,26). A further decrease below the preoperative level was seen after six months (24,25).…”
Section: Quantitative Bone Scintigraphy In Prostatic Carcinoma -Long-mentioning
confidence: 99%
“…A background ROI was chosen between the projection of the kidney and crista iliaca in order to correct for soft tissue activity in front of and behind the vertebrae (14,15). To calculate the uptake in a vertebra, measurements on a trunk simulating phantom containing a human like vertebra (made of epoxy mixed with C a H P 0 4 corresponding to a bone mineral content of 10% and a known activity of 99m Tc-MDP) were performed (14). The sensitivity of the gamma camera system was determined to 74 counts per second and MBq for " m T c in the vertebrae of interest.…”
Section: Quantitative Bone Scintigraphymentioning
confidence: 99%